1998
DOI: 10.1046/j.1523-1755.1998.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered sphingomyelinase and ceramide expression in the setting of ischemic and nephrotoxic acute renal failure

Abstract: Diverse physical and chemical stimuli can activate sphingomyelinases (SMases), resulting in sphingomyelin (SM) hydrolysis with ceramide release. Since ceramide can profoundly impact a host of homeostatic mechanisms, the concept of a "SM (or SMase) signaling pathway" has emerged. We recently documented that ceramide levels fall abruptly during renal ischemia, and then rebound to twice normal values during early reperfusion (30 to 90 min) Therefore, the present study assessed whether these ceramide changes are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 43 publications
0
57
0
Order By: Relevance
“…29,30 In contrast, oxidative stress by radiation, anticancer agents and postischemic reperfusions induces cell impairment and apoptosis through peroxidation of proteins and DNA and activation of the molecules in the death-signaling pathways. [31][32][33] Although the details of ROI-associated apoptotic signaling have not been clarified, the finding that ROIs reduce ⌬⌿ m and finally activate caspase-9 and caspase-3 is well known. [13][14][15]27 In addition, ROIs activate kinases associated with apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In contrast, oxidative stress by radiation, anticancer agents and postischemic reperfusions induces cell impairment and apoptosis through peroxidation of proteins and DNA and activation of the molecules in the death-signaling pathways. [31][32][33] Although the details of ROI-associated apoptotic signaling have not been clarified, the finding that ROIs reduce ⌬⌿ m and finally activate caspase-9 and caspase-3 is well known. [13][14][15]27 In addition, ROIs activate kinases associated with apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that hypoxia to PC12 cells results in enhanced ceramide generation through the activation of neutral sphingomyelinase (37). In contrast, other studies have shown that in ischemic injury to kidneys or cultured kidney cells the activity of sphingomyelinases is decreased rather than increased (39). Currently, there is no information on the role of ceramide synthase in the regulation of ceramide in hypoxia-reoxygenation injury.…”
mentioning
confidence: 94%
“…Although the role of ceramide has been studied in apoptotic cell death in response to a variety of stimuli, there is limited information of a role of ceramide in hypoxia-reoxygenation injury. In vivo studies of ischemic injury to the kidney (39,40) or brain (19) as well as in vitro study of hypoxic injury to cultured PC12 cells (37) have shown an increase in ceramide level. However, the cause-effect relationship between an alteration of ceramide and cytotoxicity is not known in hypoxiareoxygenation injury to renal tubular epithelial cells, and the pathways for ceramide generation in ischemia-reperfusion or hypoxia-reoxygenation injury remain to be elucidated.…”
mentioning
confidence: 99%
“…Despite the fact that a few studies in cultured PT cells have implicated ceramides as an "acute renal stress reactant" that increases in response to diverse ischemic or toxic insults (4,28,70), until now there have been no studies investigating the role of ceramides in Cd 2ϩ -induced PT cell death. Here we report for the first time that exposure to 10 -50 M Cd 2ϩ for 3-6 h induces an increased formation of cellular ceramides, which trigger apoptosis of cultured rat kidney PT cells via a calpaindependent pathway.…”
mentioning
confidence: 99%